The Image of Iraqi Women during Peaceful Demonstrations in Local Satellite Channels - Challoop, Suhad Adnan (International Journal of Psychosocial Rehabilitation, 2020)
The impact of the media in these three fields is a function closely related to the degree of the public dependency on the information it provides.The researcher believes that this theory is a comprehensive theory and provides a holistic view of the relationship between media and public opinion, and the most important thing that it added is that society effects on the media. The theory reflects the prevailing scientific tendency in social sciences to view life as a complex system of interacting elements and not merely as separate models in terms of causes and results. Identification of the problem is the most important step in the scientific research field, which scientific research is based, and the problems are often intertwined and complicated, and it is precisely that the problem can be formulated the problem, and this needs experience and knowledge from the researcher, these are matters gained by scientific and practical practice of research, and from in-depth readings. The roles that women have played in peaceful demonstrations have expressed about her awareness of political and economic reform importance in the country. The most prominent elements of the image of the woman were as a medic for the injured in the demonstrations and as a motive to the demonstrators. The majority of the families of the sample members and colleagues participated in the positive evaluation of Iraqi women, indicating the presence of a wild public opinion that participates in drawing the new image of Iraqi women. Also, the diversity of television show’s style of the channels contributed to creating a new image for Iraqi women.